Sub-0.3 volt amorphous metal WNx based NEMS switch with 8 trillion cycles - Mayet, Abdulilah Mohammad; Muqeet, Mohammed Abdul; Alhashim, Hala H.; Kurdahi, Fadi; Eftekhari-Zadeh, Ehsan (Frontiers in Materials, 2024)
Introduction: The mechanical nature of nanoelectromechanical (NEM) switches makes them sluggish yet desirable for ultra-low-power, harsh environment applications. Two- and three-terminal NEM switches have been demonstrated using onedimensional, two-dimensional, and thin films, but sub-0.3 V operation with improved mechanical and electrical reliability is still elusive. Method: This study presents WNxnano-ribbon-based NEM sensor switches that operate at 0.6 V, 30 nanosecond switching time, 8 trillion cycles, and 0.5 mA ON current with less than 5 kΩ ON resistance, without stiction, mechanical welding, or short circuits. WNx’s high Young’s modulus gives it great elasticity and mechanical restoring force, which may overcome van der Waal and capillary forces. Results and Discussion: With its high Young’s modulus, the device’s nanoscale size facilitated low operating voltage. WNxnano-ribbon without grain boundaries is amorphous and more mechanically strong. Hammering and high current flow may destroy the nano-ribbon contact surface and interface, which is practically immaculate. Pull-out time (dominant delay factor) is 0 owing to high Young’s modulus, hence hysteresis loss and delay are absent. Elasticity and Young’s modulus increase speed.